Catching a storyfish - Harrington, Janice N. (Wordsong, an imprint of Highlights, 2016)
"Keet knows the only good thing about moving away from her Alabama home is that she'll live near her beloved grandfather. When Keet starts school, it's even worse than she expected, as the kids tease her about her southern accent. Now Keet, who can 'talk the whiskers off a catfish,' doesn't want to open her mouth. Slowly, though, while fishing with her grandfather, she learns the art of listening. Gradually, she makes her first new friend. But just as she's beginning to settle in, her grandfather has a stroke, and even though he's still nearby, he suddenly feels ever-so-far-away. Keet is determined to reel him back to her by telling him stories; in the process she finds her voice and her grandfather again. This lyrical and deeply emotional novel-in-verse celebrates the power of story and of finding one's individual voice."--Publisher's website.